Sosialisasi Profesi, Jenjang Karir Bidang Kuliner Dan Cooking Demo Chocolate Praline Di SMK Adimulia Batam - Agung Arif Gunawan; Rosie Oktavia Puspita Rini; Miratia Afriani; Tirta Mulyadi (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
At this time the culinary business in Indonesia is increasingly in demand. At present the need for food and beverage is no longer a mere basic need that must be met, but has become a trend among the people. Many think that a prospect business today is the culinary business. So do not be surprised if the growth of the culinary industry in Indonesia is expected to grow and this is certainly an attractive opportunity for culinary business entrepreneurs. School is a place of education that is commonly used by everyone. At this time schools not only provide services in the form of education, but also compete to provide more services than other schools. This is intended so that the school will be more in demand by the community because of its advantages and to improve the image of the school. For this reason, schools need to convey information about the advantages they have so that they are known and known by the wider community. With the development of the culinary business which is increasingly rapid and advanced, the Batam Tourism Polytechnic strives to contribute to meeting the needs of quality human resources for the development of the culinary world at home and abroad